Corporate governance mechanisms, managerial ownership and real earnings management: Jordanian evidence - Oqlah Alkharashgah, Khaled Ahmad (2021)
An alarming rate of real earnings management (REM) in the Jordanian firms calls for concern, given the adverse effects of the practice in the long run. The weak state of corporate governance (CG) in Jordan is also considered as a critical issue, demanding for reforms of CG practices that can diminish REM. Thus, this study investigated the relationship between CG mechanisms and REM practices of non-financial firms listed on the Amman Stock Exchange (ASE). The study also tested the moderating effect of managerial ownership (MOWN) on the relationship between board of directors’ characteristics, audit committee characteristics and REM practices. The data, which covered 721 firm-year observations for the period of 7 years (2011-2017), was sourced from the annual reports of the listed non-financial companies on ASE. The results show that board characteristics (CEO duality and frequency of meeting) and audit committee characteristics (independence, expertise and frequency of meeting) are significant predictors which can mitigate REM practices in the Jordanian firms. Family ownership is also a significant determinant that mitigates REM practices, but MOWN is a weak moderating factor in the relationship between CG mechanisms and REM. The current study may help regulatory bodies and policy-makers in instituting policies and strategies with regards to the credibility of financial reports in Jordan. The study also benefits firms in formulating the best corporate strategies and improving their system controls, and the users of the financial information, especially the investors in making their financial decisions. Future studies may investigate the role that can be played by external CG mechanisms (e.g. company valuations, managerial labor market, legal implications and others) in mitigating REM activities in the companies. Also, future research can examine some external factors that may have indirect effects on the CG’s relationship with REM, as it will enrich the existing literature.